Early Detection of Reading Difficulties: Analysis of the Need for Development of Diagnostic Reading Comprehension Assessment - Rini Utari; Yeti Mulyati; Rudi Adi Nugroho; Rosita Rahma; Ayu Widiyani Sigid; Dinda Dwi Pratiwi (Universitas Pendidikan Ganesha, 2026)
Reading comprehension is fundamental to successful learning across all subjects because it is through reading that students build knowledge and develop critical and reflective thinking skills. Various assessment results indicate that students' reading comprehension abilities are still low to moderate, impacting overall academic achievement. This study aims to analyze the implementation and need for diagnostic assessment as a systematic strategy for detecting barriers to student reading comprehension using a qualitative approach and descriptive methods. Data were collected through a literature review and the distribution of questionnaires containing open-ended and closed-ended questions to junior high school students and Indonesian language teachers. The results indicate that teachers and students have positive perceptions of diagnostic assessment because it helps map initial abilities and identify difficulties, such as understanding main ideas, inferences, and vocabulary. However, its implementation is still hampered by time constraints, teacher administrative burdens, and the lack of standardized instruments. Therefore, diagnostic assessment needs to be optimized through ongoing teacher training and the development of valid and reliable instruments. This research contributes to strengthening the concept of diagnostic assessment as a formative and reflective approach, while providing a conceptual and practical basis for contextual, adaptive assessment innovations oriented toward improving national reading literacy in line with the implementation of the Independent Curriculum.